Proximal Humeral Fractures - David M. Rose MRCS; Edward G. Sutter MS; Simon C. Mears MD, PhD; Rohit R. Gupta MD, FRCS; Stephen M. Belkoff PhD (Geriatric Orthopaedic Surgery & Rehabilitation, 2010)
The purpose of our study was to biomechanically compare, under cyclic loading conditions, fracture site motion, humeral head collapse, and intra-articular hardware penetration in simulated 3-part osteoporotic proximal humeral fractures stabilized with 1 of 2 locking-plate constructs. We performed fixation on simulated 3-part proximal humeral fractures in 10 pairs of cadaveric osteoporotic humeri with a Hand Innovations S3 Proximal Humerus Plate (S3 plate) or an LCP Proximal Humerus Plate (LCP plate; 1 each for each pair). The specimens were potted, mounted on a materials testing machine, and subjected to 5000 cycles of abduction in the scapular plane, loading through the supraspinatus tendon. Interfragmentary displacement at 2 virtual points (the most medial aspect of the calcar and the most superior aspect of the osteotomy line between the greater tuberosity and humeral head) was measured using an optical tracking system. Humeral head rotation was also measured. We used a generalized linear latent and mixed model to check for an effect of cyclic loading and treatment on the parameters of interest (significance, P < .05). After cyclic loading, the S3 plate humeri showed significantly greater displacement of the greater tuberosity fragment and rotation of the humeral head and a trend (not a significant difference) toward greater displacement at the calcar. No hardware penetration was noted for either repair. Although the S3 plate repairs resulted in significantly more fracture site motion, it is unknown whether the magnitude of the motion is clinically significant.